The use of internet-mediated cross-sectional studies in mental health research. (May 2015) - Pitman, Alexandra; Osborn, David P. J.; King, Michael B.
Summary: This article summarises internet-mediated approaches to conducting quantitative and qualitative cross-sectional mental health research, and describes aspects of research design to consider for optimising scientific rigour and validity as well as response. Rapid adoption of internet-mediated approaches risks compromising the quality of the methods used. Not only can it cause distress to participants, but methodological problems may lead to inappropriate inferences being made from research findings. In this article the advantages of using internet communication for research purposes are balanced against the disadvantages, using examples of recent internet-mediated research (IMR) studies to illustrate good practice.